Exacerbation and severity of allergic symptoms during pregnancy and their impact on mental health - Kaori Yonezawa, PhD; Megumi Haruna, PhD; Kiwako Yamamoto-Hanada, MD, PhD; Yukihiro Ohya, MD, PhD (Wolters Kluwer, 2022)
Background:. Pregnant women with allergies face difficulties, as they tend to avoid medication for symptom control during pregnancy. Moreover, some women experience exacerbations during this period. These difficulties can affect their mental health. Objective:. This study aimed to investigate the factors influencing allergy exacerbations during pregnancy and examine the effects of allergy symptoms on the mental health of pregnant women. Methods:. A cross-sectional study was conducted through web-based research in March 2020, amid the COVID-19 pandemic. Pregnant women were collected from 3 groups (target: 150 participants in each group): atopic dermatitis (AD), allergic rhinitis, and without allergies. We evaluated mental health using Kessler Psychological Distress Scale (K6) and health-related quality of life using the Short Form-8 questionnaire. Results:. Overall, 202 (49.1%) of 411 pregnant women had depressive symptoms, and 45 (10.9%) had severe depressive symptoms. Women with allergies had significantly worse mental health than those without allergies. Among 119 AD patients, 36 (30.3%) experienced exacerbations during pregnancy. Of them, 11 (30.6%) did not consult a practitioner and endured the exacerbation. A significant association was observed between severe prepregnancy symptoms, job situation, coping with symptoms of AD during pregnancy, and AD exacerbation. Among 210 rhinitis patients, 17.1% experienced rhinitis exacerbation during pregnancy. The presence of rhinitis symptoms in winter and the second trimester was significantly associated with exacerbation. Conclusion:. This study revealed higher rates of depressive symptoms among pregnant women with allergies. The psychological well-being of pregnant women with AD or allergic rhinitis should be considered.